2021
DOI: 10.2319/021221-122.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term assessment of conventional and mini-screw–assisted rapid palatal expansion on the nasal cavity

Abstract: Objectives To evaluate the long-term effects of mini-screw–assisted rapid palatal expansion (MARPE), rapid palatal expansion (RPE), and controls on the nasal cavity with cone-beam computed tomography (CBCT). Materials and Methods A total of 180 CBCT scans that were part of a previous randomized trial were evaluated retrospectively for 60 patients at pretreatment (T1), postexpansion (T2), and posttreatment (T3). Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
7
1
Order By: Relevance
“…The sample size of 22 models of the subjects was set to detect an effect size coefficient of 0.8 for both palatal parameters (surface area and volume). 10 The study was approved by the ethical committee of Al-Azhar University, (approval number REC16-032), in addition to the University of Campania, Naples, Italy (approval number 24797/ 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of 22 models of the subjects was set to detect an effect size coefficient of 0.8 for both palatal parameters (surface area and volume). 10 The study was approved by the ethical committee of Al-Azhar University, (approval number REC16-032), in addition to the University of Campania, Naples, Italy (approval number 24797/ 2018).…”
Section: Methodsmentioning
confidence: 99%
“…5,9 Others have evaluated bone-borne expanders anchored only with mini-implants. 10 Such studies were designed to determine whether there was any additional orthopedic contribution to maxillary expansion by adding miniscrew anchorage at such young ages. More research is needed to investigate the potential superiority of miniscrew-supported maxillary expanders over Hyrax or Haas expanders in different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [7][8][9][10][11] have been conducted to evaluate the effects of maxillary expansion on the NS. Schwarz et al [9] suggested no significant positional change in the NS with surgically-assisted rapid maxillary expansion (SARME).…”
Section: Introductionmentioning
confidence: 99%
“…Aziz et al [10] suggested a potentially positive effect of RME on NSD during childhood but no significant change during adolescence. Recently, Mehta et al [11] concluded that rapid palatal expansion (RPE) and microimplant-assisted RPE (MARPE) significantly improved NSD in the short and long term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation